A new form of equations of motion of nonholonomic mechanical systems - Sanh, Do (Vietnam Journal of Mechanics, 1997)
In the paper it is given a new form of equations of motion of nonholonomic mechanical systems. The obtained equations are written in a matrix form and in order to establish them it is unnecessary to calculate the inverse matrix of the matrix of inertia. It is important that it is possible to obtain the relation between the error of realizing constraints and that of computing the solution of equations of motion of the system under consideration.